A proposed cloud-based billers hub using secured e-payments system - Belal Ayyoub; Bilal Zahran; Mahdi A. Nisirat; Farouq M. S. Al-Taweel; Mohammad Al Khawaldah (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2021)
Automation of several payment processes from start to end is a challenging task, particularly when multiple payments from online and offline billers are involved. In this paper, we introduced a new aggregator system to combine all billing system types, in which it is possible to pay invoices electronically. The proposed aggregator system was designed to be employed in a cloud-based Billers Hub (CBBH) developed by the central banks. Furthermore, many applications can be realized such as; deposit e-money, withdrawal e-money, and other applications. A Gateway translator is used to apply authentication rules, security, and privacy. The proposed system was employed in the Jordanian payment gateway and successfully fulfills its purpose.